Metformin regulates atrial SK2 and SK3 expression through inhibiting the PKC/ERK signaling pathway in type 2 diabetic rats - Chang-He Liu; Na Hua; Xi Fu; Yi-Long Pan; Bin Li; Xiao-Dong Li (BMC Cardiovascular Disorders, 2018)
Abstract Background Our previous study showed that metformin regulates the mRNA and protein levels of type 2 small conductance calcium-activated potassium channel (SK2) and type 3 small conductance calcium-activated potassium channels (SK3) in atrial tissue as well as the ion current of atrial myocytes in rats with type 2 diabetes mellitus (T2DM), but the underlying signaling mechanism is unknown. This study aimed to investigate whether metformin regulates atrial SK2 and SK3 protein expression in T2DM rats though the protein kinase C (PKC)/extracellular signal-regulated kinase (ERK) signaling pathway. Methods A T2DM rat model was established using a high-fat and high-sugar diet combined with a low-dose intraperitoneal injection of streptozotocin (STZ). The rats were randomly divided into the following five groups: the control group, the untreated T2DM group, the metformin-treated only group, the phorbol 12-myristate 13-acetate (PMA; a PKC agonist administered by intraperitoneal injection) treatment group, and the recombinant human epidermal growth factor (rh-EGF; an ERK agonist administered by tail vein injection) treatment group. The activity of PKC in atrial tissues was assayed by a PKC kinase activity assay kit. The protein expression of SK2, SK3, and phosphorylated ERK (pERK) were determined by western blotting and immunohistochemistry. Results Compared with the Control group, atrial PKC activity and pERK and SK3 protein expression were increased, while SK2 protein expression was decreased in atrial tissues of T2DM rats. Eight weeks of metformin treatment inhibited the PKC activity and pERK and SK3 expression, and elevated SK2 expression compared with the T2DM group. Compared with the metformin-treated only group, the injection of rh-EGF increased pERK and SK3 expression, and decreased SK2 expression; the injection of PMA increased PKC activity and SK3 expression, and decreased SK2 expression. In addition, the injection with PMA significantly elevated the expression of pERK. Conclusions The PKC/ERK signaling pathway is involved in the downregulation of SK2 expression and the upregulation of SK3 expression in the atrium of T2DM rats. Long-term metformin treatment prevents the SK2 downregulation and the SK3 upregulation through inhibiting the PKC/ERK signaling pathway.